The Effectiveness of K I P A S Counseling to Overcome Post Traumatic Stress Disorders for Elementary School Students - Nugraha, Agus Bambang; Purnomo, Andreas Wisnu Adi; Utomo, Kristoko Dwi; Ismanto, Bambang Ismanto (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
So many natural disasters that occur in 2021 will undoubtedly negatively impactuals, especially students at the elementary school level. One of the disorders caused by traumatic events is post-traumatic stress disorder (PTSD). Therefore, efforts to alleviate this matter become an urgency for educators. Seeing that BK is one of the fields engaged in helping student problems, then counseling services are one of the alternatives that need to be provided to students. In addition, seeing that who cannot separate counselling from cultural elements, efforts to treat psychic disorders that are culturally friendly should be considered and studied in depth. This study aims to determine the effectiveness of KIPAS counseling with joy-sharing techniques to overcome post-traumatic stress disorders (PTSD) of students affected by the eruption of Mount Merapi. This type of research is an experiment with a randomized pretest-posttest control group design. The research sample consisted of 14 individuals who were divided into the control group and the experimental group. The data analysis used was statistical analysis with the Mann-Whitney formula. Based on the results of the research that has been done, it is found that the sig value. 2 tailed 0.141> 0.05, which means that there is no significant effect the KIPAS counseling treatment with the excellent news sharing technique to overcome PTSD of elementary school students affected by the eruption of Mount Merapi. Bencana alam yang begitu banyak terjadi pada tahun 2021 tentunya menimbulkan dampak negatif bagi individu, terlebih lagi siswa yang duduk di jenjang sekolah dasar. Salah satu gangguan yang diakibatkan oleh peristiwa traumatis adalah post trauma stress disorders (PTSD). Oleh karena itu, upaya mengentaskan hal tersebut menjadi urgensi bagi tenaga pendidik. Melihat BK menjadi salah satu bidang yang bergerak dalam mengentaskan masalah peserta didik, maka layanan konseling menjadi salah satu alternatif yang perlu diberikan kepada siswa. Selain itu melihat konseling tidak dapat dilepaskan dari unsur budaya, maka upaya penanganan gangguan psikis yang ramah budaya menjadi hal yang patut diperhatikan dan dikaji secara mendalam. Penelitian ini bertujuan untuk mengetahui efektivitas konseling model KIPAS dengan teknik berbagi kegembiraan untuk mengatasi post traumatis stres  disorders (PTSD) siswa yang terdampak erupsi gunung Merapi. Jenis penelitian yang digunakan adalah eksperimen dengan desain randomized pretest-posttest control group. Sampel penelitian berjumlah 14 individu yang dibagi ke dalam kelompok kontrol dan kelompok eksperimen. Analisis data yang digunakan adalah analisis statistik dengan rumus Mann Whitney. Berdasarkan hasil penelitian yang telah dilakukan didapati nilai sig. 2 tailed sebesar 0.141 > 0.05, yang artinya tidak ada pengaruh yang signifikan perlakuan konseling model KIPAS dengan teknik berbagi kabar gembira untuk mengatasi PTSD siswa sekolah dasar yang terdampak erupsi gunung Merapi.